Culture matters – the training of senior civil servants in Austria, Germany, the Netherlands and Switzerland. (July 2016) - Knassmüller, Monika; Veit, Sylvia
Senior civil servants (SCS) are powerful actors with great responsibilities in the field of policymaking and management. Due to public sector reforms that are New Public Management oriented, specialised education and structured training programmes for (future) SCS as well as fast-track systems for high-potential employees have become increasingly important in many Western democracies over the last two decades. However, in several middle European countries SCS are hardly ever training participants, and furthermore, training systems have not been subject to larger reform efforts. In this article, the training of SCS in Austria, Germany, the Netherlands and Switzerland is explored, and we discuss how the observable patterns of training policies can be explained. We argue that the existence or lack of desired human resource measures such as fast-track programmes might be explained by the dominant cultural orientations in these countries. In order to systematically address, further analyse and account for observations such as the fast-track example, we apply and explore the potential of grid-group typology, developed by anthropologist Mary Douglas as part of the cultural theory approach.